2016
DOI: 10.1159/000443039
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α Signaling Pathways Involved in Mammalian Cell Fate Determination

Abstract: A diverse array of cellular stresses can lead to accumulation of misfolded or unfolded proteins in endoplasmic reticulum (ER), which subsequently elicits ER stress. Inositol-requiring enzyme 1α (IRE1α) is the most sensitive of the three unfolded protein response (UPR) branches which are triggered to cope with ER stress in mammalian cells. IRE1α signaling is quite context-specific on account of many adaptor and modulator proteins that directly interact with it, including heat shock proteins (HSPs), RING finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 93 publications
(94 reference statements)
0
39
0
Order By: Relevance
“…As we all know, TG induces ER stress and activates IRE1α, which further mediates pro-survival XBP1 splicing at the initial stage. However, if the adaptive UPR signaling pathways fail to rebalance ER homeostasis, IRE1α may promote several pro-apoptotic signaling pathways, including regulated IRE1α-dependent decay (RIDD) and IRE1α-TRAF2 axis [1]. In the present study, we found that the degree of XBP1 splicing, characterized by an increase in XBP1s and a decrease in XBP1u, was higher in TG-stimulated ECs with apocynin pretreatment when compared with TG stimulation alone.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…As we all know, TG induces ER stress and activates IRE1α, which further mediates pro-survival XBP1 splicing at the initial stage. However, if the adaptive UPR signaling pathways fail to rebalance ER homeostasis, IRE1α may promote several pro-apoptotic signaling pathways, including regulated IRE1α-dependent decay (RIDD) and IRE1α-TRAF2 axis [1]. In the present study, we found that the degree of XBP1 splicing, characterized by an increase in XBP1s and a decrease in XBP1u, was higher in TG-stimulated ECs with apocynin pretreatment when compared with TG stimulation alone.…”
Section: Discussionmentioning
confidence: 46%
“…These results suggested that IRE1α is involved in apocynin-mediated anti-apoptotic signals. Previously, we have reviewed that IRE1α-evoked XBP1 splicing promotes cell survival [1]. Therefore, we then detected the protein and mRNA expression levels of XBP1s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IRE1α also activates JNK to promote apoptosis (26). Therefore, IRE1α is involved in determination of cell fate (86). Previous studies have shown that IRE1α is activated by various virus infections, and viruses have different mechanisms to regulate IRE1α, XBP1, and JNK to facilitate their own replication.…”
Section: Discussionmentioning
confidence: 99%